Kekerasan Dalam Rumah Tangga dalam Perspektif Islam - Nur Rofiah (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
Domestic violence is often understood to refer only to physical abuse. In fact, domestic violence is related to any violence occurred in domestic life that includes: physical, sexual, and psychological violence. It also related to abandonment and threat in domestic life. Many cases of domestic violence are unreported by the victims because they considered domestic violence as a private matter. This article attempts to explore domestic violence in Islamic perspective. This article shows that domestic violence occurred as a result of an asymmetrical relationship between spouses in a marital relationship. To avoid domestic violence, the couple should attempt to build a harmonious relationship (sakinah) based on equality between the spouse.